Evaluation of air quality at the intersection of Ave. Universitaria and Panamericana Norte - Los Olivos, Lima - Valverde Flores, Jhonny Wilfredo (2016)
The present study had as a goal evaluating the Air Quality Conditions at the intersection of Ave. Universidad and Ave. Panamericana Norte, Los Olivos, Lima. For the determination of particulate material was used the technique of Gravimetry and gaseous pollutants CO and NO2 was used the technique of Ultraviolet - Visible spectroscopy. The prevailing wind was South-South-West and the speed of sedimentables atmospheric dust have a range of 12-20 km/h. In PM10 monitoring station was obtained from 137.5 g/m3, Nitrogen Dioxide (NO2) of 22.8 g/m3 and Carbon Monoxide (CO) of 5448.5 g/m3.